Cultural tolerance, positive relationships and well-being in Malaysian multicultural communities - Mitshel Lino; Intan Hashimah Mohd Hashim (Penerbit Universiti Kebangsaan Malaysia, 2020)
Taking a positive psychology perspective, this paper focuses on cultural tolerance values, positive relationships, and well-being within multicultural and pluralistic local communities in Malaysia. Participants were (n=163) undergraduates from a Malaysian public university. Eighty-three (83) were of ethnic Malay, (69) ethnic Chinese, nine ethnic Indian, and two were ethnic ‘others.’ Participants were predominantly females (122/74.8%). Participants answered an online survey comprising of open-ended qualitative questions on cultural tolerance values, positive relationships, and well-being as part of their experience living in multicultural communities. Findings indicated that participants described themselves as highly tolerant; they generally agreed that people should be allowed to practice their culture. They reported open and positive emotions (e.g. curiosity, interest, and gratefulness) and positive reactions (e.g. acceptance and respect) about others who practice different cultures. They also reported positive relationships in their communities, whereby they described the people in the community as well-connected. Using the PERMA model of well-being as the basis of analysis, participants reported a high level of wellbeing across aspects of positive emotions, engagement, relationship, meaning, and accomplishment. This study sheds some lights regarding Malaysians’ cultural tolerance values, people’s relationships within multicultural communities and community well-being.